A Critical Review on the Syllabus of “Creative Writing” Farhangian University - Fateme Jafarikamangar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Syllabus of the subject as a guideline and determinant policy of each course plays an important role in achieving its goals and competencies. The “Creative writing” course is one of the general courses of Farhangian University at the aim of improving learners’ ability to write fluently and creatively.  This study criticizes the existing syllabus and emphasizes obviating shortcomings to achieve the objectives. it is believed with minor changes, especially in the budgeting of existing course contents and the emphasis on high levels of learning, and it is possible to increase learners’ ability to create creative writing genres and to increase writing creativity in general. The statistical population of this study is the student-teachers in the field of educational sciences, the entrance of 1397 in Farhangian University of Mazandaran. The samples are three homogenized groups from among the 9 groups of students in this field. This study is applicable, and it has compared two experimental groups trained with changes in the topic of the control group who was trained exactly according to the topic by incorporating quasi-experimental method. The results showed that the scores of the experimental group in both writing creative literary types and in each element of creativity were significantly improved compared to the control group by emphasizing the need for changes or revision on the existing syllabus.